Decreased maximal aerobic capacity with use of a triphasic oral contraceptive in highly active women: a randomised controlled trial. Issue 4 (31st July 2003) - Lebrun, C M; Petit, M A; McKenzie, D C; Taunton, J E; Prior, J C
Abstract : Background: Oral contraceptives are commonly used by women athletes. However, their effect on athletic performance is unclear. Objectives: To examine the effects of a moderate dose, triphasic oral contraceptive on measures of athletic performance in highly trained women athletes. Methods: This is a double blind, placebo controlled trial in 14 women with ovulatory menstrual cycles and maximal aerobic capacity (Vo 2 max ) ≥50 ml/kg/min. Four measures of athletic performance were tested: Vo 2 max, anaerobic capacity (anaerobic speed test), aerobic endurance (time to fatigue at 90% of Vo 2 max ), and isokinetic strength (Cybex II dynamometer). Height, weight, and six skinfold measurements were also recorded. All these observational tests were completed during both the follicular and mid-luteal phases of an ovulatory menstrual cycle. Cycle phases were confirmed by assaying plasma oestradiol and progesterone. Participants were subsequently randomly assigned to either a tricyclic oral contraceptive or placebo and retested in identical fashion (oral contraceptive phase). Results: Absolute and relative changes in Vo 2 max from follicular to oral contraceptive phase decreased in the oral contraceptive group by 4.7%, whereas the placebo group showed a slight increase (+1.5%) over the same time period. Two of the women taking oral contraceptive had decreases of 4 and 9 ml/kg/min. In contrast, most women in the placebo group improved or maintained Vo 2 max . There was also a significant increase in the sum of skinfolds in women taking oral contraceptive compared with those taking placebo (p<0.01). There were no significant changes in other physiological variables (maximum ventilation, heart rate, respiratory exchange ratio, packed cell volume) or measures of performance (anaerobic speed test, aerobic endurance, isokinetic strength) as a function of oral contraceptive treatment. Conclusions: The decrease in Vo 2 max that occurs when oral contraceptive is taken may influence elite sporting performance in some women. Further studies are required to determine the mechanisms of this change.